P-299 Impact of endometriosis on responsiveness to ovarian hyperstimulation and embryo development: quantitative and qualitative aspects. (30th June 2022) - Invernici, D; Reschini, M; Benaglia, L; Somigliana, E; Galati, G; La Vecchia, I; Viganò, P; Vercellini, P
Abstract: Study question: The present study was designed to better elucidate if endometriosis may affect follicologenesis and embryo development within a cycle of ovarian hyperstimulation for IVF ( In Vitro Fertilization). Summary answer: Endometriosis women showed fewer oocytes retrieved and a higher rate of unexpected poor response albeit number of patients without good quality embryos was similar. What is known already: The pathogenetic mechanisms explaining the association between endometriosis and infertility are not fully explained. Pelvic adhesions and inflammation may play a role but other detrimental effects are presumably involved. They include reduced ovarian reserve, altered oocyte competence, impaired endometrial receptivity and association with other conditions affecting fertility such as adenomyosis. To note, even if in vitro fertilization is expected to overcome the pelvic detrimental milieu, the success rate of the procedure is lower in women with endometriosis. Study design, size, duration: We designed a clinical retrospective study in order to analyse the impact of the disease on ovarian hyperstimulation and embryo development. Women were selected among those undergoing IVF cycles between January 2014 and December 2020. The primary outcome was the number of women without top quality embryos. Secondary outcomes included the rate of unexpected poor response (retrieval of ≤ 3 oocytes), cumulative clinical pregnancy rate and cumulative birth rate. Participants/materials, setting, methods: Our study was performed at the Infertility Unit of the Fondazione IRCSS Ca' Granda Ospedale Maggiore Policlinico of Milan. We included 496 subjects with a good ovarian reserve as demonstrated by serum Anti-mullerian hormone (AMH) > 1, 1 ng/ml. Two hundreds and forty-eight women with endometriosis were identified and matched with two hundreds and forty-eight women without the disease according to age, pharmacological regimen, study period and AMH levels. Main results and the role of chance: The number of women without good quality embryos did not differ between exposed and unexposed subjects (16% vs 16%, p = 1.00). The adjusted OR was 0.85 (95%CI: 0.51-1.44, p = 0.56). The clinical pregnancy rate and the live birth rate were also similar. We observed a lower number of oocytes retrieved and a higher rate of unexpected poor response (23% vs 13%, p = 0.005) in women with endometriosis. At subgroup analysis, the higher rate of unexpected poor responders persisted only in previously operated women (27% vs 13%, p = 0.02). Limitations, reasons for caution: The evaluation of embryo quality was only based on morphological criteria. The histological diagnosis of endometriosis was lacking in unoperated women (128 subjects). Finally, our conclusions concern ovarian hyperstimulation and may not be extrapolated to natural reproductive processes. Wider implications of the findings: Despite being generally reassuring, our findings do not completely exclude some mild negative effects on folliculogenesis. Effects demonstrated could be due to anatomical distortions of the pelvis causing an inefficient response of the ovarian parenchyma to hyperstimulation. We cannot exclude that the post-surgical healing process may alter local vascular supply. Trial registration number: NA